2012
DOI: 10.1007/s12011-012-9487-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Magnesium, l-Carnitine, and Concurrent Magnesium–l-Carnitine Supplementation in Migraine Prophylaxis

Abstract: Given the conflicting results about the positive effects of magnesium and L-carnitine and as there is no report concerning concurrent supplementation of magnesium and L-carnitine on migraine prophylaxis, the effects of magnesium, L-carnitine, and concurrent magnesium-L-carnitine supplementation on migraine indicators were assessed. In this clinical trial, 133 migrainous patients were randomly assigned into three intervention groups: magnesium oxide (500 mg/day), L-carnitine (500 mg/day), and Mg-L-carnitine (50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 25 publications
1
22
0
1
Order By: Relevance
“…For the other identified potential markers, a previous study showed that low serum carnitine level might be one of the trigger of headache attack, which coincided with our study [ 25 ]. Cholecalciferol was demonstrated as down-regulated in the study, and it had been listed as a biomarker of headache in many reported studies on headache patients [ 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…For the other identified potential markers, a previous study showed that low serum carnitine level might be one of the trigger of headache attack, which coincided with our study [ 25 ]. Cholecalciferol was demonstrated as down-regulated in the study, and it had been listed as a biomarker of headache in many reported studies on headache patients [ 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…magnesium was significantly more effective at migraine relief in individuals with aura than placebo at 60 min post administration ( p < 0.05) [ 24 ]. A more recent meta-analysis by Chiu et al in 2016, reviewed a larger sample of randomized clinical trials with 11 studies investigating the effects of intravenous magnesium on acute migraines [ 19 , 20 , 21 , 25 , 26 , 27 , 28 , 29 , 30 ] and 10 studies investigating the effects of oral magnesium on migraine prophylaxis [ 16 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Using odds ratios, it was concluded that i.v.…”
Section: Resultsmentioning
confidence: 99%
“…Nine controlled clinical trials for CARN—mostly ALC—were conducted in a total of 384 patients with some neurological disorders, including Alzheimer's disease, multiple sclerosis, migraine, sciatica, fibromyalgia, chronic fatigue syndrome, and amyotrophic lateral sclerosis [ 68 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 ]. A report by Memeo and Loiero [ 68 ] compared the effects of treating sciatica patients with either ALA or ALC, and found significant protective effects from both of these agents detected as improvements from baseline in neuropathy on electromyography.…”
Section: L -Carnitine and Acetyl- Or Propionyl-mentioning
confidence: 99%
“…Tarighat Esfanjani et al [ 249 ] evaluated the effects of magnesium, CARN, and concurrent magnesium-CARN supplementation in migraine prophylaxis. Migrainous patients were randomly assigned into three intervention groups: magnesium oxide vs. CARN vs. Mg-CARN, and a control group.…”
Section: L -Carnitine and Acetyl- Or Propionyl-mentioning
confidence: 99%